Entre el retrato jurídico y la experiencia en el territorio - Darío G. Barriera (Caravelle)
This paper proposes a reflection on the distance function and its relation to the general problem of the administration of justice. It begins with a general taxonomy of different types of distance that can exist between a population and its judges, then exhumed Hispanic law tried to solve the issue of physical proximity between the Oidores and their subjects coresident (during the XVI and XVII). The purpose is to examine the regulatory treatment that the Habsburg monarchy gave the Oidores’ primary sociality for understanding the function key assigned to the distance (especially social) in the conception and execution of the colonial government during the Habsburg period.